Ultraviolet/Optical Emission of the Ionized Gas in AGN: Diagnostics of the Ionizing Source and Gas Properties - Feltre, Anna; Charlot, Stephane; Mignoli, Marco; Bongiorno, Angela; Calura, Francesco; Chevallard, Jacopo; Curtis-Lake, Emma; Gilli, Roberto; Plat, Adele (Frontiers in Astronomy and Space Sciences, 2017)
Spectroscopic studies of active galactic nuclei (AGN) are powerful means of probing the physical properties of the ionized gas within them. In particular, near future observational facilities, such as the {\itshape James Webb Space Telescope} (JWST), will allow detailed statistical studies of rest-frame ultraviolet and optical spectral features of the very distant AGN with unprecedented accuracy. In this proceedings, we discuss the various ways of exploiting new dedicated photoionization models of the narrow-line emitting regions (NLR) of AGN for the interpretation of forthcoming revolutionary datasets.